A contradição na certeza sensível - Heldt, Michele Borges (2015)
When looking for determine and identify things around, the consciousness presupposes that these things are indeterminate. Thereby, the act of thinking comes instantly in contradiction with what is thought and said, because determine something as indeterminate is a contradiction. The consciousness, in your most immediate representation, uses the certainty sensory - that is the apprehension that the same performs before making any kind of judgment about the truth or falsity of the seized thing -, looking know the truth of the object. From that point, began a game of opposites that will continue during all their development where, in an attempt to know what the object is in fact, to use its conceptual basis, the consciousness faces to universal constituent of concept about this object. And more, on universal constituent of your referential bases, the other appears to her as something fundamental to their development. That other refers to everything outside the consciousness same, as the information coming from outside that are processed internally through language and concepts. On the certainty sensory, this information appears in a contradictory way for the consciousness because what it looking is to know the object by itself and not through an external knowledge. However, is only through the concepts that consciousness will be able to know the object in its singularity. Thereby, the contradiction of determining something through universal concepts becomes also necessary in your search for knowledge. In hegelian dialectic, the contradiction not represent the impossibility of true knowledge, but is understood as a constituent part on consciousness development in your search for knowledge. However, while Hegel believes that the same should be always sublated for the development of absolute spirit, other lines of interpretation not consider that the contradiction can be eliminated in the course of dialectical movement.